The use of the Arco de Maguerez Problematization methodology in a Nursing graduation school clinic (Research, Society and Development, 2021)
Objective: To describe the experience of academics in the nursing course at Gamaliel College in view of the difficulties encountered during the curricular internship, using the Problem-solving Methodology (PM) associated with the Maguerez arch. Methodology: this is an experience report with a reflective approach, characterized by the methodology of problematization (MP) implemented through the five stages of the Arco de Maguerez. Results and Discussion: the experience resulted in the development of an objective form to control the local nursing production, in order to streamline the screening process and add information necessary to guide the local nursing care plan, in addition to providing reliable data for the academic community to develop scientific studies in the health area. Conclusion: given the above, it is understood that nursing production is an essential factor in understanding health determinants, so the development of this technology would optimize the screening time making it more efficient, directing concrete data to guide effective care plans, in addition to to promote scientific studies focused on the health area, strengthening the triad of teaching, research and important extension for the construction of knowledge to academics.